Clinical characteristics and exploratory serum biomarker findings in vestibular migraine: a cross-sectional case–control study - Bingyang Liu; Daopei Zhang; Lili Zhang; Yonghui Zhang; Xiaofang Guan (Frontiers in Neurology, 2026)
Objective Vestibular migraine (VM) is a common disorder in vertigo clinics, but its diagnosis remains challenging because of symptom overlap with other conditions and the lack of widely accepted objective biomarkers. This exploratory cross-sectional case–control study aimed to characterize the clinical features of VM, examine clinical and serum factors associated with VM case status, and assess the apparent ability of serum biomarkers to distinguish VM cases from healthy controls. Methods Between May and December 2025, 145 patients with VM and 50 healthy controls were enrolled at the First Affiliated Hospital of Henan University of Chinese Medicine. Demographic characteristics, clinical symptoms, triggering factors, family history, previous diagnoses, and self-reported medical costs were collected. Dizziness, headache impact, anxiety and depressive symptoms, and cognitive screening performance were assessed using the DHI, H-VAS, HIT-6, HAMA-14, HAMD-17, and MoCA-BJ. Serum CGRP, GDF-15, FGF-21, and IL-17 were measured in a biomarker subset of 60 VM cases and 20 healthy controls. Univariable and exploratory multivariable logistic regression analyses examined associations with VM case status, and ROC analysis assessed discrimination between VM cases and healthy controls within the biomarker development sample. Results The male-to-female ratio among VM patients was 1:6.6. Emotional fluctuations, fatigue, and sleep deprivation were frequently reported triggers. Anxiety or depression (40.0%) and cervical spondylosis (27.6%) were the most commonly reported previous diagnoses. In separate exploratory multivariable models, female sex, higher BMI, and a positive family history remained associated with VM case status in the full clinical cohort, whereas hypertension was not statistically significant after adjustment. In the biomarker subset, higher serum CGRP and GDF-15 levels remained associated with VM case status, whereas FGF-21 was not significantly associated; the apparent AUCs were 0.794 for CGRP, 0.898 for GDF-15, and 0.927 for their combination. The combined AUC was higher than that for CGRP alone (DeLong p = 0.006) but not significantly higher than that for GDF-15 alone ( p = 0.227). Conclusion VM in this single-center cohort was characterized by female predominance, recurrent symptoms, substantial symptom burden, and familial aggregation. Female sex, higher BMI, and a positive family history were clinical factors associated with VM case status after adjustment. In the biomarker subset, higher serum CGRP and GDF-15 levels were associated with VM case status, and the two biomarkers showed exploratory ability to discriminate VM cases from healthy controls.